Perceptions Of Cadets On Visual Cues And Astronomical Learning In Maritime Safety And Navigation - Chanra Purnama; Marudut Bernadtua Simanjuntak (Pusat riset dan Inovasi Nasional, 2024)
This research explores the perceptions of 40 cadets at the Transportation Institute in Jakarta regarding the application of visual cues and astronomical learning in maritime safety and navigation. Through qualitative research methods, including interviews and observational techniques, the study examines cadets' proficiency in celestial navigation, their engagement with social media and citizen science initiatives related to astronomical learning, and their awareness of cultural differences in navigation practices. The findings reveal that cadets demonstrate a high level of proficiency in celestial navigation, indicating the effectiveness of the educational practices at the Transportation Institute. However, there is room for improvement in terms of leveraging social media for educational purposes and developing cross-cultural sensitivity among cadets. The research highlights the importance of integrating practical training, fostering cross-cultural competence, and promoting a culture of lifelong learning among cadets to ensure their preparedness for the modern maritime industry. The insights gained from this research can inform educational practices and professional development initiatives in the maritime sector.